Effect of acid hydrolysis conditions on the degradation properties of cellulose from Imperata brasiliensis fibers - De Carvalho Benini, Kelly C.C. [UNESP]; Pereira, Paulo H.F. [UNESP]; Cioffi, Maria Odila H. [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP] (Elsevier, 2017)
The thermal properties of Imperata brasiliensis fibers and cellulose nanofibrils (CNFs), obtained at different conditions of sulfuric acid hydrolysis, were studied in the present work. Imperata Brasiliensis fibers were chemically treated by alkaline solution followed by bleaching treatment and both, untreated and treated fibers were characterized. Using a design of experiments (DOE), CNFs were obtained at nine different conditions, considering four factors (acid concentration, pulp/solution ratio, temperature and reaction time), at three levels. From results of thermogravimetric analysis (TGA), it was possible to determine some degradation properties and kinetic parameters such as activation energy (Ea) and understand how this parameter changes as a function of chemical treatments and acid hydrolysis conditions. Considering obtained results, it was possible to stablished that chemical treatments, carried out before acid hydrolysis, were effective since some amorphous components were removed, which was confirmed by the increase of thermal stability and Ea values. The best conditions of acid hydrolysis to obtain CNFs from Imperata brasiliensis fibers was also determined, being H2SO4 64 (wt%) at 35C for 75 min with pulp/solution ratio of 1/20 (g/mL). The suspension obtained at these conditions presented initial degradation temperature of 117 C and, Ea for the main stage of cellulose degradation of about 64 kJ/mol.
Keywords: Activation energy; Imperata brasiliensis fibers; Thermal analysis